2015
DOI: 10.1038/cdd.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 suppresses mitochondrial dysfunction of ischemic mouse livers in a mitofusin 2-dependent manner

Abstract: Ischemia/reperfusion (I/R) injury is a major cause of morbidity and mortality after liver surgery. The role of Sirtuin 1 (SIRT1) in hepatic I/R injury remains elusive. Using human and mouse livers, we investigated the effects of I/R on hepatocellular SIRT1. SIRT1 expression was significantly decreased after I/R. Genetic overexpression or pharmacological activation of SIRT1 markedly suppressed defective autophagy, onset of the mitochondrial permeability transition, and hepatocyte death after I/R, whereas SIRT1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 37 publications
(68 reference statements)
5
113
0
Order By: Relevance
“…Cells were exposed to 2 hr of simulated ischemia by exposure to anoxic Krebs‐Ringer HEPES (KRH) solution at pH 6.2. Reperfusion was then induced by reoxygenating anoxic cells in normoxic KRH at pH 7.4 for up to 2 hr (Biel et al., 2016; Kim et al., 2008; Wang et al., 2011). Propidium iodide (PI) fluorometry revealed that greater than 50% cell death occurred in old hepatocytes after 2 hr of reperfusion, while young hepatocytes withstood these conditions quite well with minimal cell death, consistent with our previous report (Wang et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cells were exposed to 2 hr of simulated ischemia by exposure to anoxic Krebs‐Ringer HEPES (KRH) solution at pH 6.2. Reperfusion was then induced by reoxygenating anoxic cells in normoxic KRH at pH 7.4 for up to 2 hr (Biel et al., 2016; Kim et al., 2008; Wang et al., 2011). Propidium iodide (PI) fluorometry revealed that greater than 50% cell death occurred in old hepatocytes after 2 hr of reperfusion, while young hepatocytes withstood these conditions quite well with minimal cell death, consistent with our previous report (Wang et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged I/R depletes young hepatocytes of SIRT1, which in turn causes necrotic cell death after reperfusion (Biel et al., 2016). To examine how short I/R affects SIRT1 in old hepatocytes, we assessed changes in SIRT1 expression before and after ischemia in young and old hepatocytes (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations